ANALYSIS OF TRENDS IN THE PERFORMANCE OF URINARY DIVERSIONS AFTER TOTAL CYSTECTOMY: A 15-YEAR EXPERIENCE - Bašić, prof. dr Dragoslav; Ignjatović, Ivan; Janković-Veličković, Ljubinka; Ignjatović, Aleksandra (Acta medicae Medianae, 2025)
The aim of our study was to analyse trends in urinary diversion (UD) in patients who underwent radical cystectomy (RC) from 2008 to 2023, with special reference to the period of the COVID-19 pandemic. A total of 283 study patients (pts) (243 men and 40 women, mean age 65.07 ± 7.73 years) were divided by the type of UD into the following groups: Mainz-pouch II (MP II) – 85 pts, ileal conduit (IC) – 89 pts, ureterocutaneostomy (UCS) – 105 pts, percutaneous nephrostomy (PCN) – 4 pts. The relative share of incontinent and continent UD was 70% and 30%, respectively. MP II was the most represented UD from 2008 to 2013, IC from 2014 to 2019, and UCS from 2019 to 2023. The most common UD was UCS (37.1%), followed by IC (31.4%), MP II (30.0%) and PCN (1.4%). Temporal UD trends were variable, with relatively stable annual shares of MP II and IC and the lowest annual share of UCS until the period of the COVID-19 pandemic, when it significantly increased, with a peak in 2022. Trend analysis shows a significant increase of UCSs in the period 2008−2023 (p < 0.001), without significant change of trends in the other groups (p > 0.05). The trends of continent and incontinent UD after RC, shown in our study, are consistent with the data reported in the current literature.